ANALISIS MANAJEMEN BISNIS SYARIAH KUALITAS PELAYANAN DAN KINERJA KARYAWAN TERHADAP KEPUASAAN KONSUMEN PT. OOCL (ORIENT OVERSEAS CONTAINER LINE) INDONESIA PADA MASA PANDEMI COVID-19 - Sutriansyah, Mohamad; Trihantana, Rully; Suryani, Ermi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
In line with improving service quality and employee performance so that the company generates profits, company survival requires an assessment of the service quality and performance of the company's employees in order to produce consumer satisfaction even during the Covid-19 pandemic. This research aims to determine and analyze consumer assessments of Service Quality and Employee Performance at PT. OOCL Indonesia, and its influence on Customer Satisfaction at PT. OOCL Indonesia. The results of this research show that there is a partially positive and significant influence between service quality on consumer satisfaction with a significant value of 0.000 <0.05 and tcount compared to ttable of 2.777 > 0.278. Apart from that, there is a positive and partially significant influence between employee performance on customer satisfaction with a significant value of 0.000 <0.05 and tcount compared to ttable of 9.547>0.278. Then there is a simultaneous positive and significant influence between service quality and employee performance on customer satisfaction with a probability value (sig) of 0.000, and a sig value < 0.05 (0.000 < 0.05). Fcount compared to Ftable is 101.815> 0.278. Sharia business management analysis, which basically positions planning, management, implementation and supervision in accordance with Islamic sharia, can be implemented in the service quality and performance of PT OOCL Indonesia employees. This is also indicated in consumer assessments of service quality and employee performance which have a positive influence on PT OOCL Indonesia consumer satisfaction.